2009
DOI: 10.15517/rbt.v58i1.5193
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms from the Colombian and Peruvian Amazon: the Genera Encyonema, Encyonopsis and Gomphonema (Cymbellales: Bacillariophyceae)

Abstract: Diatoms from the Colombian and Peruvian Amazon: the Genera Encyonema, Encyonopsis and Gomphonema (Cymbellales, Bacillariophyceae). The diatom flora of the Colombian and Peruvian Amazon is far less studied than the flora of the Brazilian sector of the basin. Here we present results related to the genera Encyonema, Encyonopsis and Gomphonema. Plankton and periphyton samples were collected in lotic and lentic waterbodies from the Amazonian-Andean region, the Amazon River, Japurá River and Porvenir River basins du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Diatom studies conducted to date, showed that this group has high diversity the same as other groups of organisms and many new taxa for science have been recently described (Vouilloud, Sala, Núñez-Avellaneda, & Duque, 2010;MontoyaMoreno, Sala, Vouilloud & Aguirre, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Diatom studies conducted to date, showed that this group has high diversity the same as other groups of organisms and many new taxa for science have been recently described (Vouilloud, Sala, Núñez-Avellaneda, & Duque, 2010;MontoyaMoreno, Sala, Vouilloud & Aguirre, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Vouilloud et al, 2010;Sala et al, 2015), Bolivia (e.g. Morales y Rivera, 2013;Morales et al, 2014), o en el mismo Perú (e.g.…”
Section: Discussionunclassified
“…Kurtkrammeria frequentis is known from various black water rivers and laguna in the Amazon region of South America (Krammer 1997b, Metzeltin & Lange-Bertalot 1998, Vouilloud et al 2010) and as a fossil in Ehrenberg material from Cayenne, Guyana, where it was reported as Cymbella aequalis (Reichardt 1995 Kurtkrammeria species are reported infrequently, primarily from mountainous regions, and consistently from oligotrophic or dystrophic waters with circumneutral pH and very low dissolved solids. Vouilloud et al (2010) report K. frequentis from rivers with pH values ranging from 5.1 to 6.3, conductivity of 10-16 µScm -1 , and low chlorophyll a content. These rivers are in a remote, undeveloped, and seldom visited area of the Amazon Basin.…”
Section: Discussionmentioning
confidence: 99%